2022
DOI: 10.1126/sciadv.abj3671
|View full text |Cite
|
Sign up to set email alerts
|

Identification of shared tumor epitopes from endogenous retroviruses inducing high-avidity cytotoxic T cells for cancer immunotherapy

Abstract: Human endogenous retroviruses (HERVs) represent 8% of the human genome. HERV products may represent tumor antigens relevant for cancer immunotherapy. We developed a bioinformatic approach to identify shared CD8 + T cell epitopes derived from cancer-associated HERVs in solid tumors. Six candidates among the most commonly shared HLA-A2 epitopes with evidence of translation were selected for immunological evaluation. In vitro priming assays confirmed the immunogenicity of these epitopes, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 67 publications
1
39
0
1
Order By: Relevance
“…We then examined whether the predicted HERV‐derived HLA‐A*02 epitopes could elicit an immune response in AML patients. We selected 8 different HLA‐A*02 epitopes among the top candidates in the additive model, focusing on peptides already identified as immunogenic in our lab (P1, P2, P4, and P6) or peptides preselected in a previous study in solid tumors but for which the immunogenicity has so far not been confirmed (P15, P16, P18, and P20) 55 . Bone marrow‐infiltrating lymphocytes (MILs) were expanded from bone marrow mononuclear cells (BMMCs) of HLA‐A*02 AML patients at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…We then examined whether the predicted HERV‐derived HLA‐A*02 epitopes could elicit an immune response in AML patients. We selected 8 different HLA‐A*02 epitopes among the top candidates in the additive model, focusing on peptides already identified as immunogenic in our lab (P1, P2, P4, and P6) or peptides preselected in a previous study in solid tumors but for which the immunogenicity has so far not been confirmed (P15, P16, P18, and P20) 55 . Bone marrow‐infiltrating lymphocytes (MILs) were expanded from bone marrow mononuclear cells (BMMCs) of HLA‐A*02 AML patients at diagnosis.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study [52] identified tumor infiltrating lymphocyte specific HERV epitopes that are translated, can bind to MHC I complex, and induce high-avidity cytotoxic T cells. In [52] as well as other previous reports [53], over expression of HERVs on tumor cells has been reported and a link to ICI response has been documented [54].…”
Section: Resultsmentioning
confidence: 99%
“…A recent study [52] identified tumor infiltrating lymphocyte specific HERV epitopes that are translated, can bind to MHC I complex, and induce high-avidity cytotoxic T cells. In [52] as well as other previous reports [53], over expression of HERVs on tumor cells has been reported and a link to ICI response has been documented [54]. To interrogate other tumor intrinsic features associated with immune response in our cohort we utilized our deep RNA sequencing (∼200 millions read/library) to quantify HERV expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, HERV-derived proteins, such as the HERV-W envelope protein, have been reported to induce cytokine production via TLR signaling [ 16 , 17 ]. Several recent reports have shown that HERV-derived proteins can also stimulate the adaptive immune system by inducing a T or B-cell response [ 18 , 19 ]. Moreover, HERV-derived long non-coding RNAs (lncRNA) can have immunostimulatory functions [ 20 ], and HERV-derived promoters or enhancers can impact the expression of inflammatory genes, which influence antiviral immunity [ 2 , 6 , 21 ].…”
Section: Introductionmentioning
confidence: 99%